2022
DOI: 10.1111/dom.14697
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the hepatoselective glucokinase activator TTP399 on ketoacidosis during insulin withdrawal in people with type 1 diabetes

Abstract: Aims: To determine the effect of TTP399, a hepatoselective glucokinase activator, on the risk of ketoacidosis during insulin withdrawal in individuals with type 1 diabetes (T1D).Materials and methods: Twenty-three participants with T1D using insulin pump therapy were randomized to 800 mg TTP399 (n = 12) or placebo (n = 11) for 7 to 10 days. After the treatment period, an insulin withdrawal test (IWT) was performed, during which insulin pumps were removed to induce ketogenesis. The IWT was stopped after 10 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The indication for TTP399 in clinical development has changed to type 1 diabetes (T1D) beginning in 2019. A phase 1b/2 adaptive study with a 12‐week treatment duration demonstrated that hepatic GK activation could simultaneously decrease HbA1c, plasma β‐hydroxybutyrate, urinary ketones, and the frequency of severe or symptomatic hypoglycemia relative to placebo 51,52 …”
Section: Clinical Exploration On Gk Targetmentioning
confidence: 99%
“…The indication for TTP399 in clinical development has changed to type 1 diabetes (T1D) beginning in 2019. A phase 1b/2 adaptive study with a 12‐week treatment duration demonstrated that hepatic GK activation could simultaneously decrease HbA1c, plasma β‐hydroxybutyrate, urinary ketones, and the frequency of severe or symptomatic hypoglycemia relative to placebo 51,52 …”
Section: Clinical Exploration On Gk Targetmentioning
confidence: 99%
“…A clinical study investigated the effect of TTP399 on the risk of ketoacidosis during insulin withdrawal in T1DM patients [ 68 ]. Participants with T1DM using insulin pump therapy were randomized to receive either 800 mg TTP399 or a placebo for 7 to 10 days.…”
Section: Ttp399 (Also Known As Cadisegliatin and Gk1-399)mentioning
confidence: 99%
“…The primary endpoint was the proportion of patients who reached beta-hydroxybutyrate (BHB) concentrations of 1 mmol/L or greater. During the treatment period, TTP399 significantly reduced mean FPG levels and resulted in fewer AEs compared to placebo treatment [ 68 ]. During the IWT, there were no differences between the TTP399 and placebo groups in the mean serum BHB concentration, mean duration of IWT, or BHB at termination of IWT.…”
Section: Ttp399 (Also Known As Cadisegliatin and Gk1-399)mentioning
confidence: 99%
See 2 more Smart Citations